A 5-Enolpyruvylshikimate 3-Phosphate Synthase Functions as a Transcriptional Repressor in Populus . Issue 7 (11th June 2018) - Xie, Meng; Muchero, Wellington; Bryan, Anthony C.; Yee, Kelsey; Guo, Hao-Bo; Zhang, Jin; Tschaplinski, Timothy J.; Singan, Vasanth R.; Lindquist, Erika; Payyavula, Raja S.; Barros-Rios, Jaime; Dixon, Richard; et al.
Abstract : An isoform of the EPSP synthase enzyme possesses a DNA-binding helix-turn-helix motif and has dual roles in shikimate biosynthesis and transcriptional repressor activity. Abstract: Long-lived perennial plants, with distinctive habits of inter-annual growth, defense, and physiology, are of great economic and ecological importance. However, some biological mechanisms resulting from genome duplication and functional divergence of genes in these systems remain poorly studied. Here, we discovered an association between a poplar ( Populus trichocarpa) 5-enolpyruvylshikimate 3-phosphate synthase gene ( PtrEPSP ) and lignin biosynthesis. Functional characterization of PtrEPSP revealed that this isoform possesses a helix-turn-helix motif in the N terminus and can function as a transcriptional repressor that regulates expression of genes in the phenylpropanoid pathway in addition to performing its canonical biosynthesis function in the shikimate pathway. We demonstrated that this isoform can localize in the nucleus and specifically binds to the promoter and represses the expression of a SLEEPER -like transcriptional regulator, which itself specifically binds to the promoter and represses the expression of PtrMYB021 (known as MYB46 in Arabidopsis thaliana ), a master regulator of the phenylpropanoid pathway and lignin biosynthesis. Analyses of overexpression and RNAi lines targeting PtrEPSP confirmed the predicted changes in PtrMYB021 expression patterns. These results demonstrate that PtrEPSP in its regulatory form and PtrhAT form a transcriptional hierarchy regulating phenylpropanoid pathway and lignin biosynthesis in Populus .